2019
DOI: 10.1111/1750-3841.14587
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulatory Activity of Dietary Phenolics Derived from Corchorus olitorius L.

Abstract: Dietary phenolics are known for their potent antioxidant and anti-inflammatory activities, making them promising candidates for protection against neuroinflammation and neurodegeneration. Hydroalcohol extract of Egyptian species of Corchorus olitorius L. (Co) leaves was investigated for its neuroprotective effects in a lipopolysaccharide-induced neuroinflammatory mouse model. Twenty five metabolites were characterized from the bioactive extract using highperformance liquid chromatography HPLC/PDA/HRESI/MS n , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…(Duncan et al., 2020; Mamat et al., 2018; Salami et al., 2016; Simion et al., 2019; Topal et al., 2016; Wagdy et al., 2019; Yang, Yu, et al., 2018)…”
Section: Chemistrymentioning
confidence: 99%
“…(Duncan et al., 2020; Mamat et al., 2018; Salami et al., 2016; Simion et al., 2019; Topal et al., 2016; Wagdy et al., 2019; Yang, Yu, et al., 2018)…”
Section: Chemistrymentioning
confidence: 99%
“…Dietary polyphenols are gaining scientific attention for their protective effects against degenerative diseases and cognitive decline due to its antioxidants properties [ 137 ]. A group of researchers revealed that hydroalcohol extract of C. olitorius leaves had inhibitory effects on neuroinflammation in a mouse model of lipopolysaccharide (LPS)-induced neuroinflammation [ 138 ]. They characterized 25 metabolites, and one of the major constituents (5.7%) was 1,5-dicaffeoylquinic acid, which significantly protected microglia from H 2 O 2 -induced cytotoxicity.…”
Section: Biological Activitymentioning
confidence: 99%
“… [ 148 ] Neuromodulatory activity C. olitorius Leaf Ethanol Extracts significantly correlated with improved cognitive function and reduced neurodegeneration induced by LPS. [ 138 ] Phytoalexin activity C. olitorius Fresh young leaf 95% ethanol Isolated stress metabolites and volatile compounds had good activity against the microorganisms. Antifungal substances are released or fungioxic compounds are synthesized in response to infection or injury.…”
Section: Biological Activitymentioning
confidence: 99%
“… 49 Additionally, 3,4-dicaffeoylquinic acid had a powerful antioxidant activity besides neuroprotective action. 50 Terpenoids are widely distributed in C. olitorius , with 18 terpenoidal compounds have been reported. Phytol diterpenoidal compounds showed antimicrobial, antioxidant and anticancer activities.…”
Section: Natural Products From C Olitoriusmentioning
confidence: 99%